Assessment of overall thoracic limb axial alignment in dogs with antebrachial deformity. Issue 8 (23rd September 2018) - Cooley, Katheryn; Kroner, Kevin; Muir, Peter; Hetzel, Scott J.; Bleedorn, Jason A.
Abstract: Objective: To assess overall thoracic limb axial alignment in dogs with and without angular limb deformity (ALD). Study design: Ex vivo and retrospective observational clinical study. Animals: Forty canine thoracic limbs from bilateral normal specimens (10 pairs) and unilateral antebrachial ALD (10 uniapical and 10 biapical deformities). Methods: Computed tomography images of the entire thoracic limb were collected for multiplanar reconstruction. Baseline limb axis was defined by the humeral anatomic axis. Axial alignment of the distal humerus, proximal and distal radius, and metacarpal bones were obtained and compared among levels and groups. Results: The mean overall thoracic limb rotation of normal dogs was 35.4 ° (95% CI, 27.2 °, 43.6 °). Mean overall limb rotation in uniapical and biapical deformity was 41.6 ° (95% CI, 33.0 °, 50.1 °) and 54.4 ° (95% CI, 45.8 °, 62.9 °), respectively, but was not statistically different ( P = .096). Only overall limb rotation in limbs with biapical ALD was different from normal limbs ( P = .008). Rotation at the level of the elbow was 77% and 85% of overall limb rotation in normal and deformity limbs, respectively, and was increased from normal in limbs with ALD (both P < .05). Radial torsion did not differ among groups but was moderately correlated with overall limb rotation. Conclusion: Rotation arising in the elbow of limbs with ALD was higher than in normal limbs and accounted for the greatest contribution of overall limb rotation. Clinical significance: Assessment of radial torsion alone is insufficient to understand overall limb axial alignment in dogs with antebrachial bone deformity.